2020
DOI: 10.1186/s12886-020-01576-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combining intravitreal injections of ranibizumab with micropulse diode laser versus intravitreal injections of ranibizumab alone in diabetic macular edema (ReCaLL): a single center, randomised, controlled, non-inferiority clinical trial

Abstract: Background To evaluate if a combination therapy with micropulse diode laser (MPL) shows non-inferiority on visual acuity (BCVA) within 12 months in comparison to standard therapy, i.e. intravitreal injection of ranibizumab alone. Setting Institutional. Prospective randomized single-center trial . Methods Patients with diabetic macular edema (DME) received three intravitreal injections of 0.5 mg ranibizumab during the upload ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…There is statistically significant higher rate of decrease in the central macular thickness in diabetic patients with macular edema who received ranibizumab alone than those who received ranibizumab and laser therapy. However, in the study of Furashova et al, 11 CMT decreased significantly in each treatment group over the study course. The effect of the treatment on CMT seems to be more prominent within the upload phase than later on and laser treatment seems not to contribute to this effect.…”
Section: Ranibizumab With Lasermentioning
confidence: 76%
See 1 more Smart Citation
“…There is statistically significant higher rate of decrease in the central macular thickness in diabetic patients with macular edema who received ranibizumab alone than those who received ranibizumab and laser therapy. However, in the study of Furashova et al, 11 CMT decreased significantly in each treatment group over the study course. The effect of the treatment on CMT seems to be more prominent within the upload phase than later on and laser treatment seems not to contribute to this effect.…”
Section: Ranibizumab With Lasermentioning
confidence: 76%
“…However, in the study of Furashova et al, 11 best corrected visual acuity (BCVA) increased statistically significant in both treatment groups till month 12. No significant differences could be found in BCVA change between the two groups at any time.…”
Section: Ranibizumab With Lasermentioning
confidence: 90%
“…Although a lower incidence of complications was reported with SML treatment compared with conventional laser treatment, SML treatment has not shown superior effectiveness [31][32][33][34]. However, the use of a combined treatment may be an effective and safe alternative for ME treatment and may reduce the number of intravitreal anti-VEGF injections required [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that fewer IVB injections were needed when laser treatment was added; however, a significant increase in BCVA was not achieved [34]. Similarly, Furashova et al reported that patients treated with ranibizumab combined with additional laser treatment experienced greater visual improvement and required fewer ranibizumab injections compared with patients treated only with ranibizumab [35].…”
Section: Diabetic Macular Edemamentioning
confidence: 99%
“…Some randomized clinical trials have demonstrated that subthreshold grid laser treatment is as effective as conventional focal/grid laser photocoagulation, though slower in terms of resolution of DME, in achieving the same functional and anatomical effects [237,238]. There have been reports of the benefits of combining SDM and intravitreal anti VEGFs in treating DME [239,240].…”
Section: Subthreshold Micropulse Diode (Sdm) Laser Photocoagulationmentioning
confidence: 99%